Born a Chief The Nineteenth Century Hopi Boyhood of Edmund Nequatewa, as told to Alfred F. Whiting - Nequatewa, Edmund, approximately 1880-1969.; Seaman, P. David; Whiting, Alfred F.; Project Muse.; Project Muse. (2019)
An account of the first twenty-two years of the life of Edmund Nequatewa on the Hopi reservation in northern Arizona.
Foreword / Carleton T. Hodge -- Autobiography. 1. Kachina. 2. Born a Chief. 3. Growing and Building in Mishongnovi. 4. Initiation at Shipaulovi. 5. Life at Shipaulovi. 6. More Moves Between Villages. 7. Experiencing Hopi Beliefs. 8. At Keams Canyon School. 9. School in Phoenix. 10. The Runaways. 11. The Scholar Returns Home. 12. The Boy Becomes a Man.
Includes bibliographical references (pages 179-188) and index.
Description based on print version record.
Keywords: Nequatewa, Edmund, -- approximately 1880-1969.; Nequatewa, Edmund, -- approximately 1880-1969 -- Childhood and youth; Hopi Indians -- Social life and customs; Hopi Indians; Hopi (Indiens) -- Biographies; Hopi Indians -- Biography; Hopi Indians -- Social life and customs; Electronic books; Electronic books